Statistical Distributions of Precipitation Data in Antalya, Turkey - Burgan, Halil Ibrahim (Proceedings of the international conference of contemporary affairs in architecture and urbanism-ICCAUA, 2021)
The estimation of precipitation data is very important while designing buildings in cities. Because of fast response of rainfall-runoff in urban areas, the stormwater infrastructure systems are developed. Especially in flood prone areas which have flash flood risks, the total precipitation, its return period and its duration should be known. For this aim, statistical distributions of long-term observed precipitation data can be determined. In this study, Antalya district which is near the Mediterranean Sea is selected as study area. The city is very crowded touristic place with more than 2.5 million local people. Antalya is one of the warmest regions in Turkey with an average daily high temperature of 25 degrees centigrade. In 6 months, the average temperatures are over 25 degrees. In the study, the best statistical distributions of precipitation data from the gauging stations near Antalya are investigated. KolmogorovSmirnov test is applied to select the best statistical distribution.